Lembar Kerja Siswa Berbasis Aktivitas Rumah Dengan Pemanfaatan Media Sekitar Anak - Tria Mardiana; Putri Meinita Triana; Sardin Sardin (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2021)
The aim of this study was to develop a product of Home Activity-Based Learning Worksheets with Utilization of Media Around Children. The research design uses the Borg and Gall R&D Model which consists of 10 implementation steps. The flow of research implementation is in the form of Research and information collection, Planning, Develop preliminary form of product, Preliminary field testing, Operational field testing, Operational product revision, Main field testing, Main Product Revision, Final Product Revision, Dissemination and implementation. Methods of data collection using interviews, observation, and questionnaires. Implementation of research at SD Karangmojo, Trirenggo, Bantul. The result of the research is the creation of a product in the form of Home Activity-Based Learning Worksheets with Utilization of Media Around Children which has been tested for its validity and effectiveness.